Vanadium aminophenolates in catechol oxidation: conformity with Finke's common catalyst hypothesis - Salonen Pasi; Savela Risto; Peuronen Anssi; Lehtonen Ari (ROYAL SOC CHEMISTRY, 2022)
Six known aminophenolate vanadium complexes V1-V6 were examined in 3,5-di-tert-butylcatechol (1, 3,5-DTBC) oxidation. From the complexes V1-V5 have been previously shown to demonstrate catechol oxidase (catecholase) like behavior, catalytically oxidizing 1 to 3,5-di-tert-butyl-1,2-benzoquinone (2, 3,5-DTBQ). A critical re-evaluation of V1-V5, including V6 not assessed earlier, in the aerobic oxidation of 1 has revealed that several catechol dioxygenase products are obtained in addition to 2, which is produced partly by autoxidation. Mechanistic investigations into the V1-V6 catalyzed oxidation of 1 by EPR, negative mode ESI-MS and V-51 NMR, in addition to semi-quantitative product distribution analyses with GC and column chromatography afford compelling evidence in support of the "common catalyst hypothesis" earlier proposed by Finke and co-workers. During the reaction, V1-V6 are partially converted in situ by H2O2 assisted leaching to vanadium catecholate complexes [V(3,5-DTBC)(2)(3,5-DTBSQ)] and [VO(3,5-DTBC)(3,5-DTBSQ)], where 3,5-DTBSQ = 3,5-di-tert-butyl-1,2-semiquinone, the latter of which has been implicated as the common true active catalyst in catechol dioxygenation as per the common catalyst hypothesis. The results herein suggest that vanadium aminophenolate complexes are sensitive to H2O2 mediated leaching in the presence of strong sigma and pi donating ligands such as 1 and 2. Furthermore, based on these results, the use of vanadium aminophenolate complexes as catechol oxidase mimics is not as warranted as previously understood.